Effect of Protein Source from Leucaena Leaves Paper Mulberry and Waterhyacinth on Growth Performance of Native Chickens - NAOYENG, Khamkeo; KANDEE, Thanousinh; PHONEGYAPHON , Vanhnasin; VANNAKHOM, Bounthan (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The experimentation aimed to studying the effect of Leucaena leaf meal, paper mulberry leaf meal and water hyacinth leaf meal on growth performance of Lao’s native chickens. This work was conducted in Souphanouvong University animal farm production. The experiment took 63 day, whilst chickens were fed. The experimentation was used 60 chickens with 8 weeks of age and average of 500 g/head divided into randomize completed block design (RCBD) with 4 treatments and 3 replication per treatment the treatment 1 as feed without plant leaf meal (T1), Treatment 2 as feed with Leucaena leaf meal (T2), Treatment 3 as feed with paper mulberry leaf meal (T3) and Treatment 4 as feed with water hyacinth leaf meal (T4). The chicken was raised individual pen with 5 chickens per pen. The results of this experiment were shown that average daily feed intake (ADFI) was shown not significant (P>0.05) when compare other treatments. However, the average dairy weight gain (ADG) and feed convert ration (FCR) showed significant (P<0.05) the result shown highest in T2 and lowest in T3. The income when compare among treatment (only calculate feed and breed cost for outcome) was highest in T2 (22,823 kip/head) and lowest T1 (16,990 kip/head). The result of this study was concluded that higher effective to ADG of native chicken when fed of Leucaena leaf meal in diet when compare with other dietary.